CHEMICAL AND ISOTOPIC EVIDENCE FOR WIDESPREAD EOARCHEAN METASEDIMENTARY ENCLAVES IN SOUTHERN WEST GREENLAND - Cates N.L.; Mojzsis S.J. (My University, 2006)
New mapping, geochemistry and zircon U-Pb ion microprobe geochronology of pre-3750 Ma rocks from West Greenland was used to identify sedimentary protoliths in a problematic high-grade metamorphic terrane. Samples were collected from southernmost part of the Itsaq Gneiss Complex where Akilia association supracrustal rocks have previously been noted. Supracrustal lithologies include laterally continuous and variably deformed units of amphibolite, ultramafics and ferruginous quartz-pyroxene rocks. Oxygen isotope and mass-independently fractionated sulfur isotopes, immobile trace elements and rare earth element patterns are consistent with origin of quartz-pyroxene rocks as chemical sediments deposited in a marine hydrothermal setting. We describe a further supracrustal lithology: Garnet-bearing quartz-biotite schists with elevated oxygen isotope values (?18OSMOW ? +16?) and mass-independently fractionated S isotopes consistent with a low-temperature aqueous sedimentary origin. In several enclaves, granitoid gneisses within low-strain limbs transect lithologic contacts and contain inclusions of surrounding rocks. This supports the interpretation that some orthogneisses were originally emplaced as igneous veins that cut supracrustal lithologies. Zircon geochronology on orthogneisses that preserve intrusive relationships confirms minimum ages of ca. 3750 Ma for the supracrustals and pooled [Th/U]zircon and ?18Ozircon values of older zircon populations are consonant with igneous growth in the bulk composition of the host rocks. Low [Zr]WR and high Zr saturation temperatures further minimize the possibility of zircon inheritance. A >3750 Ma age and chemical sedimentary origin for various Akilia association lithologies underscores the widespread occurrence of rocks of this kind beyond the type locality on Akilia (island) at the southern limit of the Itsaq Gneiss Complex. ? 2006.
Keywords: GEOCHEMISTRY; ISOTOPIC COMPOSITION; METASEDIMENTARY ROCK; TRACE ELEMENT; URANIUM-LEAD DATING; Докембрий::Архей; Precambrian::Archean